Analysis of Problem Solving Ability Judging from the Ethnicity of Junior High School Students on Social Arithmetic Materials in Singkawang City West Kalimantan - Tya Nur Sukmawati; Nurul Husna; Rika Wahyuni (Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This study aims to analyze; 1) the level of problem-solving ability of ethnic Chinese students; 2) the level of problem-solving ability of ethnic Malay students; 3) Students' problem-solving abilities based on the type of questions; 4) Differences in problem-solving abilities of ethnic Malay and Chinese students. This research method uses qualitative research. Students of ethnic Malay and ethnic Chinese class VIII at SMPN 1 Singkawang are the samples of this study. The problem-solving ability test was used as a research instrument. The data analysis technique uses an interactive (qualitative) model, namely by reducing data, presenting data, and drawing conclusions. Based on the results of this study it can be concluded; 1) The problem-solving ability of ethnic Chinese students on social arithmetic material is in the medium criteria; 2) The problem-solving ability of ethnic Malay students on social arithmetic material is in the medium criteria; 3) Based on the type of question, ethnic Malay and Chinese ethnic students are more able to work on question 1 than questions number 2 and 3; 4) there is no significant difference between ethnic Chinese and ethnic Malay students in their problem-solving abilities. Overall, the findings in this study indicate that there is no difference in problem-solving abilities between ethnic Chinese and ethnic Malay students. However, the indicator determines the plan: writing the formula that will be used in answering the questions of ethnic Malay students is superior to ethnic Chinese students.